APPLICATION OF TECHNICAL ANALYSIS ON THE CRYPTOCURRENCY MARKET - Burtnyak , I.V.; Fufalko, O. Y. (The actual problems of regional economy development, 2023)
The article substantiates the possibility of using technical analysis to research the cryptocurrency market. The work is aimed at researching the market of digital assets. The question of researching the development of the cryptocurrency market is a new scientific direction. The study of the prospects for the use of virtual money remains relevant, because with the proper improvement of technologies, legislative regulation and improvement of the relevant infrastructure, cryptocurrency will occupy a significant place in the everyday life of people, which will make it possible to reduce the circulation of cash and thereby stabilize the monetary system in general. The topicality of the topic is also due to the fact that currently the question of the feasibility of using crypto-assets remains unresolved, and cryptocurrency has taken a significant place in the brokerage market. The study of the cryptocurrency market, its regulation, influence on the financial systems of the countries of the world is gaining relevance these days. Investing in cryptocurrency is accompanied by significant risk and forces the investor to buy and sell cryptocurrency at the wrong time. Technical analysis is based on the study of historical price movement data, the identification of recurring patterns and the identification of patterns that allow predicting price changes in the near future. By implementing the application of technical analysis, investors can predict a favorable moment for buying or selling a certain coin. Technical is often used to assess the possibility of investors' reaction to what is most likely to happen in the cryptocurrency market in the future. With the help of technical analysis, it is possible to predict the state and dynamics of the cryptocurrency market, as well as make a forecast regarding the trends of changes in the pricing of cryptocurrencies. Technical analysis indicators are the result of mathematical processing of statistical data of price dynamics. One of the main aspects of technical analysis is subjectivity, the analyst analyzes data on price behavior in the past and predicts pricing for the future, which enables a significant part to make a trading decision. Techniques of technical analysis are a key tool for market analysis, which allows you to understand when and which assets should be bought and when to sell.